2002
DOI: 10.1097/00006534-200205000-00022
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Effects on Breast Reconstruction with the Deep Inferior Epigastric Perforator Flap

Abstract: Immediate breast reconstruction has important advantages over delayed reconstruction, including a shorter operative time and decreased psychological distress for the patient. However, the authors' experiences with the deep inferior epigastric perforator flap demonstrate variable aesthetic outcomes among patients who undergo radiation postoperatively. To establish an association between radiation and poor postoperative results, a matched-pairs analysis was conducted. Thirty irradiated patients were paired with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
158
0
5

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 240 publications
(171 citation statements)
references
References 11 publications
6
158
0
5
Order By: Relevance
“…Most studies find that radiotherapy in an implant-based reconstruction increases complications and late failure rates (5,(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). The results of the present study are in line with those of other studies in this field (5,(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)30,31,33).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Most studies find that radiotherapy in an implant-based reconstruction increases complications and late failure rates (5,(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). The results of the present study are in line with those of other studies in this field (5,(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)30,31,33).…”
Section: Discussionsupporting
confidence: 91%
“…Radiotherapy after mastectomy but before reconstruction has not been shown to increase complications after autologous reconstruction (25); however, not all studies are in agreement (26,27). Certain studies show that postoperative radiotherapy to the breast reconstructed with a deep inferior epigastric perforator flap (DIEP) or transverse rectus abdominis myocutaneous (TRAM) flap has no effect on the reconstruction (28,29), while several others show a considerable negative effect on the final results of autologous reconstruction (24,26,(30)(31)(32)(33)(34).…”
Section: The Effect Of Radiotherapy On Breast Reconstructionmentioning
confidence: 99%
“…In the study of Motwani et al it was concluded that immediate breast reconstruction poses challenges for the treatment planning of post mastectomy radiation therapy because of suboptimal field coverage and organ protection (19). Also, patients who have their breast reconstructed before their radiotherapy are exposed to increased late complication rates (20) and unpredictable outcomes (21) due to which the timing of breast reconstruction has to be planned carefully. Patients that receive radiotherapy after DIEP-flap reconstruction show significantly increased rates of fat necrosis, fibrosis and contracture (21), similar applies to implant based reconstruction (22,23).…”
Section: Discussionmentioning
confidence: 99%
“…Breast reconstruction in the patient requiring radiation therapy There is substantial risk to the reconstructed breast undergoing radiation (7)(8)(9)(10). In autologous reconstruction, flaps can shrink and develop contour abnormalities.…”
Section: Discussionmentioning
confidence: 99%